The Effect of Financial Literacy, Lifestyle, and Use of M-Banking on Financial Management Moderated by Socioeconomic Status Among Millennials in Pontianak City - Ananda Shalsa Qirani; Heni Safitri; Dedi Hariyanto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze and explain the influence of financial literacy, lifestyle, and use of M-Banking on financial management, considering socioeconomic status as a moderating variable among millennials in Pontianak City. This study uses a quantitative approach with an associative research design, and data collection was conducted through the distribution of questionnaires to 150 respondents who met the purposive sampling criteria. Data analysis was performed through validity and reliability tests, classical assumption tests, as well as multiple linear regression and Moderated Regression Analysis (MRA) to determine the role of socioeconomic status as a moderating variable. The results indicate that, partially, financial literacy and use M-Banking have a positive and significant influence on millennials' financial management. Conversely, lifestyle does not show a statistically significant influence. Simultaneously, the three independent variables were found to have a significant effect on financial management. In addition, socioeconomic status was found to moderate the effect of financial literacy on financial management, but did not moderate the effect of lifestyle or use M-Banking. The coefficient of determination (R²) value of 79.7% indicates that the variation in financial management in this model can be explained by the combination of variables used, while the rest is influenced by factors outside the model.